(untitled) (Práxis Educativa, 2020)
This paper aims to analyze the progress of conservative education policies in the Brazilian High School. For this analysis, the Secondary School Reform (Law no. 13.145/2017) and the Programa Novos Caminhos (New Paths Program) are considered. In methodological terms, bibliographic research and document analysis procedures are utilized, based on a qualitative approach. The results reveal that the analyzed policies are instruments that revitalize the historical duality that marks the education of young Brazilians and, aligned with the interests of the capitalist society and the perverse logic of neoliberalism, these policies crave an education geared towards precarious education and qualification of workforce for the market. Therefore, those policies do not have a dialogue with the interests of the working class, which needs comprehensive education that offers, in addition to production of life, conditions for effective human emancipation. Keywords: Conservative policies. High School Reform. Programa Novos Caminhos.